THE EVIDENCE OF NON N-GLYCAN LINKED MANNOSE IN EXOCHITINASE (42 kDa) FROM Trichoderma harzianum BIO10671 GLYCOSYLATION - Muskhazli Mustafa; Faridah Qamaruz Zaman; Salfarina Ramli; Nor Farizan Tohfah; Nalisha Ithnin; Greg Wallis (Universitas Gadjah Mada, 2008)
Chitinase 42 kDa produced by Trichoderma harzianum has been proven as a prime compound to be excreted onto the hyphae of the pathogen causing localised cell wall lysis at the point of interaction. This finally initiate the process of the host cell becomes empty of cytoplasm, disintegrates and shows a rapid collapse. This study investigates the existence of N-glycan linked mannose in chitinase 42 kDa produced by the Malaysian T. harzianum strain BIO10671. The chitinase 42 kDa from T. harzianum BIO10671 was initially purified using anion exchange chromatography prior to a series of experiments such as immunoblotting against the chitinase 42 kDa antibody, lectin staining for detecting any terminal linked mannose, and galactofuranose detection to determine the presence of galatofuranose components in glycoproteins. The enzyme purification harvested about 12-fold of chitinase 42 kDa from T. harzianum BIO10671 with strong indication of the presence chitinase 42 kDa presence on SDS-Page. This was confirmed by immunoblotting with a strong response around 42 kDa after overnight incubation in chitinase 42 kDa antibody suggesting that the gene for chitinase 42 kDa was greatly expressed in this strain. There are no intervation of galatofuranose on any of the terminal mannose in chitinase 42 kDa as shown by negative results on samples treated with or without endoglycosidase-H and lectin staining. Therefore, it can be concludeed that glycosylation occurred in the chitinase 42 kDa from T. harzianum 42 kDa was not in the form of N-glycan linked mannose as expected.